Social media strategies used to translate knowledge and disseminate clinical neuroscience information to healthcare users: A systematic review. - Rachel Victoria Baran; Melissa Fazari; David Lightfoot; Michael David Cusimano (PLOS Digital Health)
Social media can be an important source of clinical neuroscience information for healthcare users (e.g., patients, healthcare providers, the general public). This systematic review synthesized evidence on the effectiveness of social media strategies in translating knowledge and disseminating clinical neuroscience information to healthcare users. A systematic review of six electronic databases up to July 29, 2024 was conducted. Original, peer-reviewed articles examining the effectiveness of YouTube, Facebook, LinkedIn, Twitter, social media messaging apps, or a combination of these platforms in translating clinical neuroscience information to healthcare users (e.g., patients, healthcare providers, caregivers, and the general public) were eligible for inclusion. Several proxies (e.g., change in uptake of research, change in awareness, change in knowledge, change in understanding, behaviour change, and/or change in social media metrics) were considered as outcomes of knowledge translation (KT) effectiveness. Two independent reviewers screened articles and assessed risk of bias. The protocol was registered on PROSPERO (ID: CRD42021269034). A total of six studies were included in this review. The included studies used YouTube, Facebook, Twitter, or a combination of social media platforms aimed at healthcare users. Most social media strategies used to disseminate clinical neuroscience information in the included studies (N = 5/6) resulted in improved indicators of KT. However, due to the high risk of bias among the included studies, these results must be interpreted with caution. Disseminating clinical neuroscience information via Facebook, Twitter, YouTube, or a combination of these platforms may achieve the goals of KT. However, there is currently a gap in the literature about clinical neuroscience KT via social media, both in the quantity of studies and quality of evidence. Future research should aim to minimize the risk of bias by controlling for important confounding factors and use objective measures of KT to complement subjective measures.